Regular consumption of a cocoa product improves the cardiometabolic profile in healthy and moderately hypercholesterolaemic adults - Sarriá, Beatriz; Martínez-López, Sara; Sierra-Cinos, José Luis; García-Diz, Luis; Mateos, Raquel; Bravo, Laura (British journal of nutrition, 2014)
Cocoa products present great health potential due to their high content of polyphenols, mainly of flavanols. However, the antioxidant, anti-inflammatory and other health effects of regularly consuming cocoa products seem to depend on the intake and health status of the consumer, etc. and need to be further clarified. A randomised, controlled, cross-over, free-living study was carried out in healthy (n 24) and moderately hypercholesterolaemic (>2000 mg/l, n 20) subjects to assess the influence of regularly consuming (4 weeks) two servings (15 g each) of a cocoa product rich in fibre (containing 33·9 % of total dietary fibre (TDF) and 13·9 mg/g of soluble polyphenols) in milk v. consuming only milk (control) on (1) serum lipid and lipoprotein profile, (2) serum malondialdehyde levels, carbonyl groups, ferric reducing/antioxidant power, oxygen radical absorbance capacity and free radical-scavenging capacity, (3) IL-1β, IL-6, TNF-α, IL-10, IL-8, monocyte chemoattractant protein-1, and vascular and intracellular cell adhesion molecule levels, and (4) systolic and diastolic blood pressure and heart rate. Throughout the study, the diet and physical activity of the volunteers, as well as any possible changes in weight or other anthropometric parameters, were also evaluated. The intake of TDF increased (P< 0·001) to the recommended levels. Serum HDL-cholesterol (HDL-C) levels were increased (P< 0·001), whereas glucose (P= 0·029), IL-1β (P= 0·001) and IL-10 (P= 0·001) levels were decreased. The rest of the studied cardiovascular parameters, as well as the anthropometric ones, remained similar. In conclusion, regularly consuming a cocoa product with milk improves cardiovascular health by increasing HDL-C levels and inducing hypoglycaemic and anti-inflammatory effects in healthy and hypercholesterolaemic individuals without causing weight gain.